EFFECT OF LONG-TERM TILLAGE AND NITROGEN FERTILIZATION ON SOIL AGGREGATE STABILITY IN MUNG BEAN CULTIVATION AT TEACHING FARM LAMPUNG STATE POLYTECHNIC - Afrianti, Nur Afni; Nugrahani, Aliya; Afandi, Afandi; Banuwa, Irwan Sukri; Arif, M. A. Syamsul; Zaqyah, Irene (Jurnal Agrotek Tropika, 2025)
The long-term intensive use of agricultural land is often associated with the degradation of soil physical quality, especially aggregate stability. This study aims to examine the effect of long-term tillage practices and nitrogen fertilization on soil aggregate stability in mung bean (Vigna radiata L.) cultivation at the Teaching Farm of Lampung State Polytechnic. This study is part of a long-term experiment in its 33rd year, conducted from September 2020 to February 2021. Soil analysis was carried out at the Soil Science Laboratory, Faculty of Agriculture, University of Lampung. The study employed a factorial Randomized Complete Block Design (RCBD) with a 2 × 3 factorial arrangement and four replications. The first factor was nitrogen fertilization (N0 = no nitrogen application, N2 = 50 kg N ha⁻¹). The second factor was long-term tillage treatment (T1 = Intensive Tillage, T2 = Minimum Tillage, T3 = No Tillage). The primary variable observed was soil aggregate stability, assessed using both dry and wet sieving methods. Supporting variables included mung bean yield and mung bean root dry weight. The observed data were initially tested using Bartlett's Test (for homogeneity of variance) and Tukey's Test (for additivity of data). If the assumptions were fulfilled, the data were analyzed using analysis of variance (ANOVA). If significant effects were indicated, further analysis was conducted using Duncan's New Multiple Range Test (DMRT) at the 5% significance level. The results of the study showed that soil aggregate stability under the no-tillage treatment was significantly higher than under the other tillage treatments. Nitrogen fertilization and the interaction between nitrogen fertilization and tillage systems had no significant effect on soil aggregate stability.